Analysis of shiping activity and water quality in the Silugonggo Juwana River Channel - Indah Saraswati; Sutrisno Anggoro; Dian Wijayanto; Andi Prasetiawan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The role of the river as a site for riverine activities has a huge impact on the economic sustainability of the community and the riverine ecosystem. The Silugonggo River is the only river in Pati Regency that is a very densely populated shipping route. This research was conducted along the Silugonggo River from the Juwana Bridge to the estuary. The purpose of this study was to determine ship activity in the Silugonggo River, determine the feasibility of facilities at Juwana Port and analyze environmental conditions along the Silugonggo River. The method used is a qualitative method with observation techniques and laboratory analysis, which is carried out by observing and recording conditions in the field systematically using primary data in the form of water conditions and secondary data in the form of ship activity and construction data. The results showed that the activities in the port of Juwana include mooring, loading and unloading of goods, ship repair and refuelling of ships. The level of water pollution in the Silugonggo River at 5 sampling points shows that the oil content in the water for points 1, 3, 4 and 5 is still considered safe because it is below the quality standard, but the oil content at point 2 has a very high value from the set quality standard which is 20 mg/L. The pollution that occurs is caused by shipping activities that dump waste into the water and fuel filling activities.Keywords:marine polutionportriverwater qualityoil spill